2022
DOI: 10.1111/petr.14364
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the risk factors for BK virus‐associated hemorrhagic cystitis in pediatric bone marrow transplantation patients: Does post‐transplantation cyclophosphamide increase the frequency?

Abstract: Background BKV‐HC is one of the most significant complications of HSCT. This retrospective study aimed to determine the frequency of BKV‐HC in pediatric patients undergoing HSCT, detect the associated risk factors for the development of BKV‐HC, and explore the effects of post‐transplantation Cy use. Methods Three hundred twenty‐seven patients (girls: 121, boys: 206) were analyzed according to sex, conditioning regimen, transplantation type, donor relatedness, stem cell source, the presence and grade of aGVHD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this regard, it has been reported that the rates of infection by BK virus and CMV reactivation are significantly lower in these groups. Particularly, in the study by Ersoy et al (2023) [ 37 ] the frequency of BK virus infection was 9.2% in the high donor compatibility whereas the frequency was higher in the mismatch (9.7%) and the haploidentical (19.3%) groups. Similar results were reported by Atay et al (2018) [ 36 ] where the frequency of BK virus infection was lower in the high donor compatibility group (31%) than in the mismatch and haploidentical groups (37.5% and 38.7%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been reported that the rates of infection by BK virus and CMV reactivation are significantly lower in these groups. Particularly, in the study by Ersoy et al (2023) [ 37 ] the frequency of BK virus infection was 9.2% in the high donor compatibility whereas the frequency was higher in the mismatch (9.7%) and the haploidentical (19.3%) groups. Similar results were reported by Atay et al (2018) [ 36 ] where the frequency of BK virus infection was lower in the high donor compatibility group (31%) than in the mismatch and haploidentical groups (37.5% and 38.7%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, until there is comprehensive evidence about the additive effects of postCy on GvHD control or superiority to ATG in MUD transplants, we suggest that postCy is not recommended in MUD pediatric transplants because of the risk of increased immunosuppression. Viral reactivations have been reported, including cytomegalovirus, Epstein Barr virus (11) and BKV-related grade 4 hemorrhage cystitis (14). Viral reactivations should be monitored closely and treated promptly.…”
Section: Discussionmentioning
confidence: 99%
“…One of these complications is thromboembolic events, which can have various underlying causes ( 3 ). Additionally, patients undergoing HSCT may experience hemorrhagic complications, such as diffuse alveolar hemorrhage and hemorrhagic cystitis ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%